Pengaruh Model Teams Games Tournament (TGT) Berbantuan Media Ular Tangga untuk Pemahaman Konsep Siswa pada Pelajaran IPA Kelas 4 SD Negeri Bakalrejo 01 - Bela Apriliana Rahayu; Ela Suryani (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
This study aims to determine the effect of the TGT model with the help of snakes and ladders media for understanding student concepts in science class 4 at SDN Bakalrejo 01. The design of this study was experimental. The population in this study were students of SDN Bakalrejo 01, the samples in this study were students in grades 4A and 4B. The data analysis techniques in this study were normality test, homogeneity test, independent t-test, and simple linear regression test. The results showed: 1) There were differences in understanding of the concepts of 4th grade students at SDN Bakalrejo 01 after using the TGT model with the help of snake and ladder media in science lessons, which was proven by a significance value of 0.008 <0.05. 2) There is an effect of the TGT model assisted by the snake and ladder media on the understanding of the concepts of the 4th grade students of SDN Bakalrejo 01 in science lessons as evidenced by the significance value of 0.032 <0.05. science lessons.